2002
DOI: 10.1046/j.1365-2141.2002.03636.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony‐stimulating factor mobilized whole blood containing over 0·3 × 106/kg CD34+ cells is a sufficient graft in autologous transplantation for relapsed non‐Hodgkin's lymphoma

Abstract: Summary. The feasibility of unprocessed, granulocyte colony-stimulating factor (G-CSF)-mobilized whole blood (WB) as an alternative stem cell source for autologous stem cell transplantation was studied. Forty-seven relapsed nonHodgkin's lymphoma (NHL) patients entered the study. After two or three ifosfamide, methotrexate and etoposide (IMVP) courses, 1 l of G-CSF-mobilized WB was collected and stored refrigerated for 72 h. Meanwhile, BAM conditioning was given: BCNU (carmustine) 300 mg/m 2 , highdose cytarabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Accordingly, we found similar neutrophil recovery after either mobilized WB or PBPC support after a BEAM (carmustine, etoposide, cytarabine, and melphalan)‐like regimen despite a 10 to 20 times lower CD34+ cell dose in the mobilized WB group 8 . Still, better mobilization regimes 9‐11 are required to increase CD34+ cell numbers in order to extend the number of eligible patients and to improve platelet recovery, which was slightly delayed in the mobilized WB group in comparison with that in PBPC transplants 8 . Concerning the limited storage time of mobilized WB, we have recently demonstrated that prolonged storage of WB for 7 days is feasible at 22°C by using a calcium‐free Leibovitz's L15 medium as a supplement to the standard anticoagulant citrate 12 .…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Accordingly, we found similar neutrophil recovery after either mobilized WB or PBPC support after a BEAM (carmustine, etoposide, cytarabine, and melphalan)‐like regimen despite a 10 to 20 times lower CD34+ cell dose in the mobilized WB group 8 . Still, better mobilization regimes 9‐11 are required to increase CD34+ cell numbers in order to extend the number of eligible patients and to improve platelet recovery, which was slightly delayed in the mobilized WB group in comparison with that in PBPC transplants 8 . Concerning the limited storage time of mobilized WB, we have recently demonstrated that prolonged storage of WB for 7 days is feasible at 22°C by using a calcium‐free Leibovitz's L15 medium as a supplement to the standard anticoagulant citrate 12 .…”
supporting
confidence: 62%
“…Considering the CD34+ cell dose, the generally accepted cell dose of >2.0 × 10 6 per kg may not be required for mobilized WB, as extensive apoptosis after cryopreservation reduces the transplanted CD34+ cell dose of leukapheresis components, whereas extensive apoptosis does not happen during liquid storage of mobilized WB 6,7 . Accordingly, we found similar neutrophil recovery after either mobilized WB or PBPC support after a BEAM (carmustine, etoposide, cytarabine, and melphalan)‐like regimen despite a 10 to 20 times lower CD34+ cell dose in the mobilized WB group 8 . Still, better mobilization regimes 9‐11 are required to increase CD34+ cell numbers in order to extend the number of eligible patients and to improve platelet recovery, which was slightly delayed in the mobilized WB group in comparison with that in PBPC transplants 8 .…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The nadir leukocyte and platelet counts and the duration of leukopenia and thrombocytopenia were comparable to our experience in patients with non-Hodgkin lymphomas and multiple myeloma undergoing ASCT after a combination of carmustine, etoposide, cytarabine, and melphalan (BEAM) or high-dose melphalan (HDM; 200 mg/m 2 ). 32 Because there is no standard conditioning regimen for ASCT used in autoimmune disease, 33 a standard regimen from our institution was used. Fludarabine induces T-cell depletion and the alkylating agent melphalan was used to achieve myeloablation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, a very low number of PBPCs will lead to delayed recovery of platelets (PLTs) and, to a much lesser degree, granulocytes. 1,2,4,8 Various measures have been used to document the concentration of PBPCs in PBPC products. A poor correlation was found between the total number of infused mononuclear cells and hematologic recovery.…”
Section: Introductionmentioning
confidence: 99%